Perempuan dalam Belenggu Kuasa: Subalternitas Roro Oyi dalam Sastra Lisan Makam Banyusumurup - Ajeng Aisyah Fitria (Tambo: Journal of Manuscript and Oral Tradition, 2026)
Concubines in the Mataram Kingdom played an important role as a form of legitimization. The more concubines there were, the more offspring were born, which signified the greatness of a king. This is found in the oral literature of the origin of the Banyusumurup Tomb with the story of Roro Oyi as Amangkurat I's concubine. The purpose of this research is to reveal Roro Oyi as a subaltern in the oral literature and to explain the powers that shackled women during Amangkurat I's reign. Data is analyzed using Gayatri Spivak's subaltern theory and Antonio Gramsci's hegemony theory. This paper used descriptive qualitative method with data retrieval techniques using observation, interviews, and listening and recording techniques. The result of this research is that Roro Oyi is a subaltern group who cannot speak. Her last attempt to speak was when Roro Oyi committed suicide. The patriarchal society and differences in social strata put Roro Oyi in a lower class. This was exacerbated by the hegemony and domination exercised by Amangkurat I. The assumption that the king was the representative of God led to Amangkurat I's absolutism.